Analisis Materi IPA Pada Buku Siswa Kurikulum 2013 Kelas V Sekolah Dasar Ditinjau Dari Standar Isi Dan Pendekatan Saintifik - Saputri, Mulat Kurnianingsih Dwi; , Nur Amalia, S.S., M.Teach (2017)
This study aims 1) to determine the suitability of Science materials in the student book in 2013 curricullum the fifth grade of primary school in terms of Content Standards. 2) describe the suitability of Science materials in the student book in 2013 curricullum the fifth grade of primary school in terms of scientific approach. The research is a qualitative research design with a content analysis study. Data collection techniques used were documentation and observation. The data obtained are tested its validity by triangulation. The data obtained are checked repeatedly and be checked by the professionals. The results showed that the suitability of the Science material in terms of Content Standards have compatibility of 96,67% in a category of very appropriate. 2) The result of the analysis of the suitability of Scine materials in grade fifth student's book of 2013 curriculum. In term of scientific approch are a) observation with 73 activities ( 24,7%), b) questioning with 60 acctivities ( 20,3%), c) Thingking with 54 activities (18,2%), d) experiment with 68 activities (22,9%), e) Comunicate with 41 activities (13,9%). The student's book have strengths and weaknesses, so the teacher must know the quality of the book in order to teacher effectively.